Diagnosis and treatment of the rare procedural complication of malpositioned pacing leads in the left heart: a single center experience. (31st December 2022) - Borgquist, Rasmus; Farouq, Maiwand; Markstad, Hanna; Brandt, Johan; Mörtsell, David; Jensen, Steen; Chaudhry, Uzma; Wang, Lingwei
Abstract: Objectives . This study assessed the management approach and outcome of the pacemaker or implantable cardioverter-defibrillator (ICD) leads malpositioned in the left heart. Malpositioned leads (MPLs) may have deleterious consequences, and appropriate management remains uncertain. Methods . The study population included all patients referred to a single institution for MPL in the left side of the heart after pacemaker or ICD implantation during the period from 2015 to 2021. The approach and outcome of lead management were retrospectively assessed. Results . During the study period, 6887 patients underwent device implantation. MPL was diagnosed in five patients (0.07%). In four cases, the pacing lead was placed in a coronary sinus (CS) branch, while the pacing lead was inside the left ventricle (LV) in one case. Symptoms suggestive of lead malposition were reported by 2 patients (40%). One of the patients presented with recurrent TIAs. Another presented with inappropriate ICD shocks. In one asymptomatic case, an ICD lead changed position from the right ventricle to the CS, suggesting idiopathic lead migration. In 4/5 patients, the leads were removed or repositioned by percutaneous approach, with no major periprocedural complications. Conclusions . In this series of MPL in the left heart, two patients presented with thromboembolic events or inappropriate ICD shocks. These serious complications highlight the critical need for early correct diagnosis and proper management of MPL.